Transition urbaine et électrification domestique en Afrique de l’Est: La diversification énergétique des périphéries de Dar Es Salaam - Rémi de Bercegol (Territoire en Mouvement)
In the remote districts of the Dar Es Salaam periphery, low density and urban sprawl do not facilitate connection to basic urban infrastructures. Through the analysis of the district of Ilala, this article focuses on the modalities and effects of electrification of these areas located at the end of the network. Strongly supported by the inhabitants, TANESCO's access to electricity is finally made possible, thanks to the subsidized extension of its networks, thus quickly relegating the few off-grid backup electrical systems (generators, solar systems). But counter-intuitively, the arrival of electricity does not mean that other pre-existing energy sources (such as kerosene and coal) disappear. In these intermediate areas between the city and the countryside, there is rather an 'energy diversification', resulting from the widening of the available offers: users quickly adopt electricity to access new services more easily (television, refrigerator, light bulb) while continuing to prefer non-electric energy for other domestic uses (cooking and ironing with coal, for example; or occasional lighting and rapid cooking with kerosene). Less expensive, easily available, requiring minimal equipment, these so-called traditional energies will continue to be used alongside new exclusively electrical uses. This diversification is neglected in the country's energy strategy, which focuses on electricity despite the financial difficulties in implementing it. Documented in the literature, the explanatory factors of household fuel choices are usually centered on user practices, but more rarely placed in a broader perspective of understanding energy governance. By revealing the structural factors of energy diversification in intermediate spaces undergoing electrification, this article contributes to the reflections on the particularities of the energy transition in order to better understand the particularities of African urbanization.